Hamburg: The Cradle of British Rock - Clayson, Alan (London Sanctuary Publishing Ltd, 1997)
A frank and often brutal account of how British idols-in-waiting served their apprenticeship for fame in Hamburg: the music, the personalities, the club scene, the sex, the prostitution, the drugs, the return home.
Keywords: 20th Century (1901-2000); Popular music; Music history; Hamburg (Germany)